Inhibition of Tunneling Nanotube (TNT) Formation and Human T-cell Leukemia Virus Type 1 (HTLV-1) Transmission by Cytarabine - Omsland, Maria (Sci Rep, 2018)
The human T-cell leukemia virus type 1 (HTLV-1) is highly dependent on cell-to-cell interaction for transmission and productive infection. Cell-to-cell interactions through the virological synapse, biofilm-like structures and cellular conduits have been reported, but the relative contribution of each mechanism on HTLV-1 transmission still remains vastly unknown. The HTLV-1 protein p8 has been found to increase viral transmission and cellular conduits. Here we show that HTLV-1 expressing cells are interconnected by tunneling nanotubes (TNTs) defined as thin structures containing F-actin and lack of tubulin connecting two cells. TNTs connected HTLV-1 expressing cells and uninfected T-cells and monocytes and the viral proteins Tax and Gag localized to these TNTs. The HTLV-1 expressing protein p8 was found to induce TNT formation. Treatment of MT-2 cells with the nucleoside analog cytarabine (cytosine arabinoside, AraC) reduced number of TNTs and furthermore reduced TNT formation induced by the p8 protein. Intercellular transmission of HTLV-1 through TNTs provides a means of escape from recognition by the immune system. Cytarabine could represent a novel anti-HTLV-1 drug interfering with viral transmission.